Effect of Initial Sugar Concentration on the Production of L (+) Lactic Acid by Simultaneous Enzymatic Hydrolysis and Fermentation of an Agro-Industrial Waste Product of Pineapple (Ananas comosus) Using Lactobacillus casei Subspecies rhamnosus - Araya-Cloutier, Carla; Rojas-Garbanzo, Carolina; Velázquez-Carrillo, Carmela (International Journal of Biotechnology for Wellness Industries, 2012)
Production of lactic acid by fermentation process has been studied from glucose solutions and other sources because of many important reasons: biotechnological production is cheaper than chemical synthesis; production of biodegradable materials from L (+) lactic acid and, the use of nutrient-rich agro-industrial wastes as raw material, which helps to reduce the environmental impact. The goal of this study was to evaluate the effect of sugar concentration of a pineapple liquid waste as the carbon source on the capacity of Lactobacillus casei subspecies rhamnosus to produce lactic acid by simultaneous enzymatic hydrolysis and fermentation. Three different pineapple waste concentrations were evaluated (60, 80 and 100% v/v) from a pineapple juice with 11.3% (m/v) of sugars (sucrose, fructose and glucose). L. casei was able to consume all sugars present within the levels tested, and converted all into lactic acid, showing efficient yields of 0.91 g lactic acid/g sugars. Final lactic acid concentration increased significantly (p<0.05) with the increase of pineapple waste percentage. Maximum lactic acid concentration (102g/L) was achieved with 100% pineapple waste medium. The highest total productivity (4.0g/h) and volumetric productivity (4.48 g/L*h) were obtained with 60% pineapple waste medium and it decreased significantly (p<0.05) when 100% was used. Fermentation time increased with the increment of sugars, and it increased significantly with the medium composed of 100% of pineapple waste in comparison with the other two media. Pineapple waste represents a good alternative as a cheap carbon source for bacterial growth and production of L (+) lactic acid.